2019
DOI: 10.1103/physrevb.99.205140
|View full text |Cite
|
Sign up to set email alerts
|

Non-Wigner-Dyson level statistics and fractal wave function of disordered Weyl semimetals

Abstract: Finding fingerprints of disordered Weyl semimetals (WSMs) is an unsolved task. Here we report such findings in the level statistics and the fractal nature of electron wavefunction around Weyl nodes of disordered WSMs. The nearest-neighbor level spacing follows a new universal distribution P c (s) = C 1 s 2 exp[−C 2 s 2−γ 0 ] originally proposed for the level statistics of critical states in the integer quantum Hall systems or normal dirty metals (diffusive metals) at metal-to-insulator transitions, instead of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…If there exists an ALT from extended states to localized states when disorder strength W varies for a fixed E, the correlation length ξ diverges at the critical value W c as ξ(W) ∝ |W − W c | −ν . p 2 near W c satisfies the following oneparameter scaling function [55][56][57]…”
Section: Model and Methodsmentioning
confidence: 99%
“…If there exists an ALT from extended states to localized states when disorder strength W varies for a fixed E, the correlation length ξ diverges at the critical value W c as ξ(W) ∝ |W − W c | −ν . p 2 near W c satisfies the following oneparameter scaling function [55][56][57]…”
Section: Model and Methodsmentioning
confidence: 99%
“…1, there are two more phases: the WSMs characterized by paired Weyl nodes in the clean limit and the normal gapped insulators. Noticeably, the phase boundary of the disordered WSMs is still an issue under debate, e.g., whether the WSMs can exist in finite disorders [52] and whether there is a direct WSM-to-DM transition without the intermediated Chern insulator phase [47,48,53] or two quantum phase transitions of WSM-to-CI-to-DM with increasing disorders [55]. However, this challenging problem is not the focus of this paper.…”
Section: Dm-to-aimentioning
confidence: 97%
“…To investigate the nature of this Anderson localization transition and its associated universality class, we compute the PR p 2 (E = 0, W ), which measures how many lattice sites are occupied by the wave function of E = 0 [49][50][51]. Near the critical disorder W c3 of the Anderson localization transitions, p 2 satisfies the one-parameter scaling function [52,53],…”
Section: Dm-to-aimentioning
confidence: 99%
See 1 more Smart Citation
“…In semimetals, the instantonic contribution ρ smooth to the DoS may be exponentially suppressed by the small deviation |d − d c | of the dimension d from the critical dimension d c = 2γ of the transition or the number of the particle flavours [17]. Even in the absence of small parameters, various numerical studies of 3D Weyl and Dirac semimetals have found this contribution to be rather small or unobservable [17,[54][55][56][65][66][67][68][69], which allows one to use the DoS, to a good approximation, as an order parameter for the transition. It has also been suggested [14] that the instantonic contribution may broaden criticality, thus converting the transition to a sharp crossover.…”
mentioning
confidence: 99%